Bioelectronics: Plasmon‐Enhanced Photocurrent of Photosynthetic Pigment Proteins on Nanoporous Silver (Adv. Funct. Mater. 2/2016). (January 2016) - Friebe, Vincent M.; Delgado, Juan D.; Swainsbury, David J. K.; Gruber, J. Michael; Chanaewa, Alina; van Grondelle, Rienk; von Hauff, Elizabeth; Millo, Diego; Jones, Michael R.; Frese, Raoul N.
Abstract : The highest photocurrent to date on a bare metal electrode is reported by R. N. Frese and co‐workers. Plasmon‐enhanced light harvesting in a photosynthetic pigment protein on a nanoporous silver substrate results in record photocurrents up to 416 μA cm −2, representing a breakthrough in the field of biohybrid photoelectrodes. This is significant for the development of potential bioelectronic devices such as biohybrid solar cells and biosensors.